"Rescue Sells": Narrating Human Trafficking to Evangelical Populists. Issue 3 (3rd July 2019) - Swartz, David R.
Abstract: The antitrafficking movement in Southeast Asia suggests shifting evangelical approaches to social justice. American activists on the ground have moved away from "rescue" toward greater indigeneity and attention to social structures. Populist evangelicals back home, however, resist these new methods. They too want to address deep injustices in the world, but they do so with an emotive individualism and American triumphalism that drives a vocabulary of rescue. In a kind of bargain, humanitarians adopt structural methods even as they continue to narrate rescue for an American constituency overflowing with money, energy, and potential recruits. That "rescue sells" offers insight into how populists and cosmopolitans negotiate power and imagine authority in starkly divided evangelical networks.